SOME DATA ON POND SNAILS (MOLLUSCA: GASTROPODA: LYMNAEIDAE) OF THE NAURZUM RESERVE (KOSTANAY OBLAST, KAZAKHSTAN) - Bragina, T.M. (PUBLISHINGS of Kostanay State Pedagogical University, 2020)
he paper contains some data on species of the pulmonate familiy Lymnaeidae of the Naurzum Reserve (Kostanay Oblast, Kazakhstan). Most species are recorded from the waterbodies of the reserve. 9 species are included on the check-list with description of species ranges and distribution based on the own gatherings and literature data. The malacological collection is located in the Science-Research Center on Ecology and Biology of the Kostanay State Pedagogical University named after Umirzak Sultangazin (Kostanay, Kazakhstan)
Keywords: malacofauna; gastropoda; mollusca; lymnaeidae; check-list; Naurzum reserve; Kostanay oblast; Kazakhstan